2014
DOI: 10.1371/journal.pone.0108987
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Validity of Job Exposure Matrix for Psychosocial Factors at Work

Abstract: ObjectiveTo study the performance of a developed job exposure matrix (JEM) for the assessment of psychosocial factors at work in terms of accuracy, possible misclassification bias and predictive ability to detect known associations with depression and low back pain (LBP).Materials and MethodsWe utilized two large population surveys (the Health 2000 Study and the Finnish Work and Health Surveys), one to construct the JEM and another to test matrix performance. In the first study, information on job demands, job… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 36 publications
4
49
3
1
Order By: Relevance
“…This is a common source bias in cross-sectional studies with self-reported health outcomes, introducing risk of differential misclassification, and in this case an over estimation of the true modifying effect of social support. This is particularly an issue when measuring exposures and outcomes simultaneously (59). However, our data did not show any association between levels of social support and reporting of LBPi.…”
Section: Strengths and Limitationscontrasting
confidence: 80%
“…This is a common source bias in cross-sectional studies with self-reported health outcomes, introducing risk of differential misclassification, and in this case an over estimation of the true modifying effect of social support. This is particularly an issue when measuring exposures and outcomes simultaneously (59). However, our data did not show any association between levels of social support and reporting of LBPi.…”
Section: Strengths and Limitationscontrasting
confidence: 80%
“…below the median). It has been used successfully to predict risk of cardiovascular disease and of major mental disorders [87]. Low social support may further increase the risk associated with job strain [85,88].…”
Section: Methods Of Assessment and Classificationmentioning
confidence: 99%
“…Through application of such a matrix to data from Finnish National Health and Work Surveys, it was possible, for example, to demonstrate significant associations of low back pain with monotonous work, although odds ratios were only about 1.2 [87].…”
Section: Vargas-prada and Coggon Pagementioning
confidence: 99%
“…We would argue that the most important work environment assessment is provided by the subject, even though we cannot exclude the fact that high levels of pain and disability influence the perception of work demand, which subsequently is misclassified [34,37]. In that case, we would expect the pain and disability change scores to be associated with changes in the work factors.…”
Section: Determinants For Individual-level Changes In the Demand Conmentioning
confidence: 97%
“…Consequently, we did not expect the average score of the decision or learning demands to change in a patient population with different occupations. In previous studies, subjective job control has been found to be highly correlated with objective job control data (based upon expert ratings or average group assessments) among workers [33,34]. As such, there is less reason to believe that job control will change significantly in the course of 1 year, even in a patient population.…”
Section: Changes In Demand Control and Support At The 1-year Follow-upmentioning
confidence: 97%